A Comparative Study of Efficacy and Adverse Effects Between Alfuzosin and Tamsulosin in the Treatment of Benign Prostatic Hyperplasia - Rahman, Md Mizanur; Alam, SM Mahbub; Amin, Md Nurul (Ibrahim Cardiac Medical Journal, 2011)
Keywords: Tamsulosin, alfuzosin; lower urinary tract symptoms; benign prostatic hyperplasia Ibrahim Card Med J 2011; 1(1):27-32